PENINGKATAN KETERAMPILAN MENGUBAH PUISI KE DALAM BENTUK PROSA MENGGUNAKAN METODE HYPNOTEACHING DI KELAS VI - Ramadhani, Sari (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe the improvement of skills in changing poetry into prose using the Hypnoteaching method in the sixth grade of elementary school. This type of research is PTK using qualitative and quantitative approaches. This research was carried out at SD Negeri 35 Parak Karakah, Padang City with a total of 23 students consisting of 12 male students and 11 female students. In Pre-Writing Cycle I obtained an average score of 48.9 (K), increasing in cycle II to obtain an average score of 89 (SB), at the writing stage of the first cycle, the average value of 49 (K) was increased in the second cycle to obtain a score on average 83 (B), in the post-writing phase of cycle I, the average value of 49 (K) increases in cycle II, obtaining an average score of 83 (SB). Keywords: Increased, changing poetry into prose, hypnoteaching method.